Analgesic and Anti-Inflammatory Effects of an Extract and Flavonoids from Artemisia Herba-Alba and Their Mechanisms of Action - Qnais, E.; Raad, D.; Bseiso, Y. (Нейрофизиология, 2014)
Artemisia herba-alba (A. h.-a.) has wide use in traditional medicine for the relief of coughing, healing external wounds, and treatment of pain associated with gastrointestinal disturbances. We investigated in vivo antinociceptive and anti-inflammatory activities of an aqueous extract (aq. ex.) and two isolated compounds obtained from aerial parts of A. h.-a. The analgesic effects of aq. ex. (10, 31.6, 100, 316, and 1000 mg/kg), astragalin, and eupatilin (both, 0.316, 1, 3.16, 10, 31.6, and 100 mg/kg) were studied using the hot-plate test in mice and formalin test in rats. The effects were compared with those of 5 mg/kg morphine. Dosedependent analgesic effects of aq. ex., astragalin, and eupatilin were clearly manifested in both hot-plate assay and early and late phases of formalin-induced paw licking. These effects were significantly but partly reduced by the opioid receptor antagonist naloxone (5 mg/kg). The same range of doses of aq. ex., astragalin, and eupatilin caused dose-dependent suppression of carrageenan-induced paw edema in rats. Thus, we demonstrated that A. h.-a. possesses noticeable antinociceptive and anti-inflammatory activities; our data support the reasons for using this plant as a remedy for treatment of pain and inflammation. Antinociceptive and anti-inflammatory actions of A. h.-a. are considerably related to the presence of astragalin and eupatilin